Strategic Corporate Layoffs - Agarwal, Ruchir (IMF Working Papers; Working Paper ;, 2016)
Firms in the S and P 500 often announce layoffs within days of one another, despite the fact that the average S and P 500 constituent announces layoffs once every 5 years. By contrast, similarsized privately-held firms do not behave in this way. This paper provides empirical evidence that such clustering behavior is largely due to CEOs managing their reputation in financial markets. To interpret these results we develop a theoretical framework in which managers delay layoffs during good economic states to avoid damaging the markets perception of their ability. The model predicts clustering in the timing of layoff announcements, and illustrates a mechanism through which the cyclicality of firms layoff policies is amplified. Our findings suggest that reputation management is an important driver of layoff policies both at daily frequencies and over the business cycle, and can have significant macroeconomic consequences.